Determining pediatric hypertension criteria: concordance between observed physician methods and guideline-recommended methods. Issue 9 (6th September 2021) - Turer, Christy B.; Doney, Analise; Bowen, Michael E.; Menzies, Christopher; Gheen, William T.; Bhat, Deepa; Fish, Jason; Barlow, Sarah E.; Skinner, Celette S.; Lehmann, Christoph U.
Abstract : Objective: To determine and evaluate the accuracy of methods physicians use to detect diagnostic criteria for pediatric hypertension [hypertensive blood pressures (BPs) on three or more occasions] in electronic health records (EHRs). Methods: Methods used by pediatric-trained physicians ( n  = 12) to detect diagnostic criteria for hypertension in a simulation using a child's EHR data were directly observed, timed, and evaluated for accuracy. All physicians were given the same information regarding diagnostic criteria to eliminate knowledge gaps. Then, computer modeling and EHR data from 41 654 3–18-year-olds were used to simulate and compare the accuracy of detecting hypertension criteria using an observed-shorthand method vs. the guideline-recommended/gold-standard method. Results: No physician used the guideline-recommended method of determining multiple time-of-care hypertension thresholds for child age/height at the time of each BP measure. One physician estimated the child's BP diagnosis without computing thresholds; 11 of 12 physicians determined the child's hypertension threshold from age/height data at the time of a current visit and applied/imputed this threshold to BP measured at all visits (current-visit threshold used to assess historical-visit BPs) to detect three separate BP elevations. Physicians took 2.3 min (95% confidence interval, 1.5–3.0) to declare a diagnosis. Sensitivity was 83.1% when applying the current-visit threshold to detect the guideline-recommended-BP-threshold diagnosis using EHR data. Specificity and positive-predictive/negative-predictive values ranged from 98.5 to 99.9%. Conclusion: Physicians applied a shorthand method to evaluate pediatric BPs. Computer-simulated comparison of the shorthand and guideline methods using clinical data suggest the shorthand method could yield an inaccurate impression of a child's BP history in 17% of pediatric ambulatory visits.